Genetic variation in sensation affects food liking and intake. (December 2021) - Feeney, Emma L; McGuinness, Lauren; Hayes, John E; Nolden, Alissa A
Highlights: Food liking, choices and intake are influenced by many factors, including genetics. The human repertoire of taste, odor and chemesthetic receptors has much variation. Many variants are known to influence flavor and/or liking and intake. Heterogeneity across studies: (cohorts, methods), present interpretation challenges. Introduction of standard methods will offer new opportunities for understanding. Abstract : Three separate sensory systems — taste, smell, and chemesthesis — contribute to the overall flavor perception of foods and beverages. Modern psychophysical methods have led to quantitation of individual differences in perception, which have potentially important implications for food liking and intake, along with human health. Carefully designed studies using contemporary methods have allowed for the identification of novel relationships between variability in chemosensory and related genes with differences in perception, liking, and intake of foods and beverages. Here we summarize recent original research on relationships between chemosensory genetics and various measures of food liking and intake.